Riba dalam Al-Qur’an: Analisis Komparatif Muhammad Abduh dan Quraish Shihab - Husain, Fandi; Amar, Rizki (AHKAM, 2024)
Usury "excess" is a transaction that scholars firmly agree on its prohibition. The problem then is whether every double (adh'âfan mudh'afah) is categorised as usury, this then raises various interpretations by the mufassir both classical and contemporary scholars today. This research seeks to explore the concept of usury according to the understanding of Muhammad Abduh as the foundation of modern-contemporary tafsir and M. Quraish Shihab as a contemporary tafsir. This type of research is library research (librari reseach) with a descriptive-comparative research model, and focuses on tafsir Al-Manar and tafsir Al-Mishbah as primary sources. While tafsir books, articles-journals, dictionaries, web pages, as secondary sources. The results showed that Muhammad Abduh argued that usury is forbidden which is multiple and contains elements of exploitation as it happened in pre-Islamic times. And he allows usury that contains benefits. While M. Quraish Shihab interprets usury as "excess" which contains elements of persecution and oppression so it is prohibited. Both agree on the dangers posed by usury and even Shihab quotes Abduh's expression that the usurer can be considered a disbeliever.